Scientific evidence on mental health in nursing professionals in the hospital setting - Palomino-Limaylla, Victoria-del-Carmen (2022)
Nowadays, given the pandemic situation caused by COVID 19, it has become clear that health personnel are at high risk of presenting emotional problems due to the uncertainty of the potential risks of the hospital environment. Objective: To determine the scientific evidence on mental health in nursing professionals in the hospital context. Method: Integrative, exploratory review in 2 databases, Dialnet and Google Scholar, considering the inclusion criteria as English, Spanish and Portuguese. Results. There is evidence of an increase in the presence of mental health problems in nurses, such as stress, anxiety, depression, fear, among others. In the face of unknown highly contagious illnesses that have appeared in recent years, which places them at high occupational risk and affects the quality of life of the professionals responsible for care. It is concluded that, in the face of the health emergency, nurses should use biosecurity and personal protection measures in health practice, such as taking care of their mental health, in order to maintain an adequate relationship involving patient-nurse care. It also favours timely preventive interventions in the mental health care of nurses.